Anthropogenic nutrient pollution of coral reefs in Southern Bahia, Brazil - Ozeas S. Costa Jr. (Brazilian Journal of Oceanography, 2007)
Spatial, temporal and anthropogenic controls on nutrient distribution were evaluated for nearshore and offshore reefs at Porto Seguro Bay, Southern Bahia. Water samples were analysed for total oxidised nitrogen (TON), soluble reactive phosphorus (SRP), reactive silica (DSi), and chlorophyll a (Chl). The results indicate that rainfall promotes a significant (F=19.873, p<0.001) increase in the load of nutrients to nearshore (average 12% increase) and offshore reefs (average 31% increase). Nutrient concentrations at the urbanized reef (TON=1.93-3.21µM; SRP=0.57-0.89µM; DSi=8.48-11.15µM) are on average 25% higher than at non-urban reefs and over 200% higher than the offshore reef. The urbanized reef also presented the highest rates of increase in nutrient input between dry and rainy seasons (TON=+0.36µM; SRP=+0.08µM; DSi=+0.70µM). Differences in nutrient concentration between nearshore and offshore reefs are more pronounced during dry season, when the bulk of land-based nutrient contribution is confined to the nearshore reefs. SRP values in the study area ranked among the highest in the world for coral reef areas and phytoplankton growth appears to be nitrogen-limited. Este artigo discute os fatores espaço, tempo e atividade antrópica na distribuição de nutrientes em amostras dos recifes costeiros da Baía de Porto Seguro, sul do Estado da Bahia. Análises realizadas nas amostras d'água incluem a porção reativa de nitrogênio (TON), fósforo (SRP) e silicato (DSi) dissolvidos, e clorofila (Chl). Resultados indicam um aumento significante (F=19.873, p<0.001) na descarga de nutrientes durante a estação chuvosa para os recifes costeiros (média de 12%) e para o recife oceânico (média de 31%). O recife urbano (TON=1.93-3.21µM; SRP=0.57-0.89µM; DSi=8.48-11.15µM) apresentou concentrações 25% mais altas que o outro recife costeiro, e mais de 200% acima do recife oceânico. Aquele recife também apresentou as mais altas taxas de aumento na descarga de nutrientes entre as estações seca e chuvosa (TON=+0.36µM; SRP=+0.08µM; DSi=+0.70µM). A diferença nas concentrações de nutrientes entre os recifes costeiros e oceânico é maior durante a estação seca, quando a contribuição continental de nutrientes está confinada a áreas próximo à costa. As concentrações de fósforo inorgânico na área de estudo estão entre as mais altas do mundo para áreas coralinas, e o fitoplâncton parece ser limitado pela disponibilidade de nitrogênio.